IMPLEMENTASI KERJA SAMA ANTARA INDONESIA DAN KOREA SELATAN MELALUI INDONESIA-KOREA COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IK-CEPA) - Hakin, Rana Ashila Hamasda Hakin; Taqwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
IK-CEPA or as known as Indonesia-Korea Comprehensive Economic Partnership Agreement, is an agreement reached between Indonesia and South Korea with the aim of eliminating trade barriers, facilitating investment, and strengthening economic cooperation. This study uses a qualitative method with a case study approach to collect and analyze data from secondary sources. Secondary data is obtained from various sources such as books, documents, newspapers, journals, and websites concerning all data about the expansion of IK-CEPA. The theory used in this research is the theory of international trade, viewed from the perspective of liberalism, using the nation-state level of analysis. The results of the study show that the implementation of this agreement through trade between the two countries provides better market access with tariff reductions that significantly benefit import and export activities in both countries, although its implementation in 2023 showed a slight decline in trade value compared to 2022. This was due to the post COVID-19 economic impact and a lack of understanding regarding the agreement. The strategies that can be implemented to optimize the benefits of IK-CEPA include enhancing cooperation and knowledge among businesspeople from both countries. The existence of the IK-CEPA free trade agreement is expected to optimize the expansion of both import and export activities, thereby boosting the economies of Indonesia and South Korea. Keywords : Indonesia-Korea Comprehensive Economic Partnership Agreement (IK-CEPA), International Cooperation, International Trade.